Review of the leafhopper genus Jilinga Ghauri (Hemiptera: Cicadellidae: Deltocephalinae: Paralimnini), with description of two new species from China - Xing, Ji-Chun; Viraktamath, C. A.; Dai, Ren-Huai; Li, Zi-Zhong (Zootaxa, 2012)
The leafhopper genus Jilinga Ghauri (Cicadellidae: Deltocephalinae: Paralimnini) is reported for the first time from Chinaand two new species, Jilinga linzhiensis sp. nov. and Jilinga asymmetrica sp. nov. are described and illustrated. A key is given to distinguish all species of the genus.